Development and processing of high temperature and low field colossal magnetoresistance materials - Zhang, Yuebin. (2008)
Colossal magnetoresistance (CMR) materials developed in 1994 promise to increase the sensitivities of the hard disk drive (HDD) heads by orders of magnitude over today's state of the art. CMR materials have aroused much interest due to the discovery of their unusually large magnetoresistance upon a transition from paramagnetic insulator to ferromagnetic metal with decrease of temperature. However, low operating temperature and high saturation magnetic field restrict their applications in reading heads of HDD. To fabricate the high temperature and low field CMR materials, it is necessary to understand the CMR behavior.